Peningkatan Keterampilan Mengelola Emosi Marah Melalui Strategi Emotional Literacy - Fitrianingsih Fitrianingsih; Blasius Boli Lasan; Henny Indreswari (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: The purpose of this study is to determine the effectiveness of emotinal literacy strategies through group guidance to improve the skills to manage angry emotions in students of SMPN 5 Kendari. The approach used is quantitative with a quasi-experimental design that is pretest-posttest with control group design. The sample selection in this research is purposive sampling technique. Data analysis used the Wilcoxon test to find out the increased skills in managing angry emotions before and after the intervention was given and the Mann Whitney U Test was used to test whether there were differences between the two intervention groups. Based on the results of the analysis showed that emotional literacy strategies through effective group guidance to improve anger emotion management skills in students of SMPN 5 Kendari.                                                                                                      Abstrak: Tujuan penelitian ini yaitu untuk mengetahui keefektifan strategi emotional literacy melalui bimbingan kelompok untuk meningkatkan keterampilan mengelola emosi dengan desain kuasi eksperimen yaitu pretest-posttest with control group design. Pemilihan sampel dalam penelitian yaitu teknik purposive sampling. Analisis data menggunakan uji Wilcoxon untuk mengetahui peningkatan keterampilan mengelola emosi marah sebelum dan setelah diberikan intervensi dan uji Mann Whitney U Test untuk menguji apakah ada perbedaan antara kedua kelompok intervensi. Berdasarkan hasil analisis menunjukkan bahwa strategi emotional literacy melalui bimbingan kelompok efektif untuk meningkatkan keterampilan mengelola emosi marah pada siswa SMPN 5 Kendari.